2008
DOI: 10.1021/jp802526z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and High Performance of La2O3−V2O5/MCM-41 Catalysts for Ethylbenzene Dehydrogenation in the Presence of CO2

Abstract: A series of La 2 O 3 -V 2 O 5 /MCM-41 catalysts with high specific surface area were prepared by means of incipient wetness impregnation for the dehydrogenation of ethylbenzene to styrene using CO 2 as oxidant. At 600°C, the conversion of ethylbenzene and selectivity to styrene over 10La15V/MCM-41 after an on-stream time of 4 h was about 86.5 and 91.0%, respectively. The properties of the catalysts before and after the reaction were characterized using techniques such as X-ray diffraction, specific surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…The objective of the present study is to prepare mesoporous silica supported vanadia catalysts with superior catalytic performance. A vanadia catalyst supported on a mesoporous silica such as MCM-41 and SBA-15 exhibited good performance for the dehydrogenation of ethylbenzene with CO2 [20][21][22][23]. Following this observation, in the present work, VOx/SBA-15 catalysts were prepared by using mesoporous SBA-15 as the support.…”
Section: Introductionmentioning
confidence: 77%
“…The objective of the present study is to prepare mesoporous silica supported vanadia catalysts with superior catalytic performance. A vanadia catalyst supported on a mesoporous silica such as MCM-41 and SBA-15 exhibited good performance for the dehydrogenation of ethylbenzene with CO2 [20][21][22][23]. Following this observation, in the present work, VOx/SBA-15 catalysts were prepared by using mesoporous SBA-15 as the support.…”
Section: Introductionmentioning
confidence: 77%
“…1. The pure MCM-41 exhibits strong peaks at 2<theta> = 2.1°due to (1 0 0) reflection lines, three weak signals at 2<theta> = 3.56, 4.08 and 5.4°that correspond to (1 1 0), (2 0 0), and (2 1 0) reflections, indicating the formation of well-ordered hexagonal mesoporous material with space group p6mm [13][14][15]. The X-RD patterns of SZr-MCM41(A-C) also showed typical diffraction peaks at 2<theta> = 2.2, 3.8 and 4.4°, which are slightly higher than the 2<theta> value of pure siliceous MCM-41.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…3B, the O 1s peaks of fresh and used LaMeO x /M41 are asymmetrical and the existence of shoulders in the region of low BE should be a result of overlapping of O 1s peaks originated from La 2 O 3 (528.6 eV) [25], CoO (or ZnO, Fe 2 O 3 ) (ca. 530.2 eV) and SiO 2 (532.8 eV) [26]. Based on the XPS results, the higher ratios of La/ Si or Me/Si on the surface than stoichiometric value of sorbents suggested that the active species is highly dispersed in the channels of M41.…”
Section: Xps Resultsmentioning
confidence: 98%